Schoolchildren’s Compensatory Strategies and Skills in Relation to Attention and Executive Function App Training - Rossignoli-Palomeque, Teresa; Quiros-Godoy, María; Perez-Hernandez, Elena; González-Marqués, Javier (Frontiers in Psychology, 2019)
Background: Given the importance of attention and executive functions (EF) in children’s behavior, programs aimed at improving these processes are of special interest. Nexxo-training combines the use of the Nexxo touchscreen application (inhibition and vigilance tasks) with self-monitoring strategies for the whole group, plus compensatory strategies based on individual child performance. This study presents an analysis of the compensatory strategies that schoolchildren receive when experiencing difficulties with EF tasks, in addition to an analysis of the developmental factors and cognitive skills that may modulate EF task performance. Method: we use data from a previous randomized active-controlled study (under review), in which forty-six typically developing children aged between 6 and 8 years old (24 girls/22 boys) were enrolled in the training group. The selected children were in the 1st grade (n =28, x ̅ = 78.32 ±4.037 months) and 3rd grade of primary education (n =18, x ̅ =102.11 ±3.445). We collected data on training performance, compensatory strategies needed and neuropsychological assessments. Results: those who had lower scores in EF training needed more compensatory strategies, particularly, instructional comprehension (r= -.684, p < .001 for inhibition-tasks; r= -.552, p < .001 for attention-tasks). Age significantly predicted better performance in both tasks (β= .295, p < .001 for inhibition; β= .816, p < .001 for attention). Those with higher scores in inhibition also had higher scores in attention (r = .72, p < .001). Participants with higher performance in fluid intelligence (Q1, n=12) had higher scores (U= 14.5, p < .05) than the group with the lowest performance (Q4, n=11) in attention. Conclusion: inhibition is one of the core processes of EF. Therefore, we should focus training on the core EF processes. Inhibition and attention are closely related. Compensatory strategies are more needed for participants with lower levels of performance. Instructional comprehension and self-instruction seem to be the most useful strategies for those with difficulties. Age moderates task performance. Fluid intelligence predicted better results in attention. EF training using not only an app, but compensatory strategies based on user performance, is a new research direction offering more opportunities to generalize EF training.